Upaya Kiai Menghidupkan Pendidikan Islam di Dusun 02 Kampung Kota Baru Padang Ratu Lampung Tengah - Lilis Setiya Ningsih; Husnul Mu’amalah; Bahrudin Yusuf Zen (Al-Bustan: Jurnal Pendidikan Islam, 2024)
The actions taken by clerics to strengthen Islamic education in certain areas, such as Hamlet 02 in Kota Baru Village, Padang Ratu District, Central Lampung Regency in 2023, are various efforts aimed at developing and improving understanding and religious practices among the local community. The purpose of this study was to determine the efforts made by kiai in reviving Islamic education in hamlet 02 Kampung Kota Baru, Padang Ratu District, Central Lampung Regency. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. Then proceed with analyzing the data through a system of data reduction, data presentation and conclusion drawing. The results showed that the kiai's efforts in reviving Islamic education in hamlet 02 through TPA Pondok Pesantren Baitussalam, namely by holding activities, namely Riyadah, recitation of mothers, simaan al-Qur'an, and grouping the ability of students into various classes. And there are inhibiting and supporting factors, the inhibiting factor is the lack of desire and low awareness of the community to learn Islam, while the supporting factor is funding, financial support also comes from him to develop and revive Islamic education.